PENYULUHAN HUKUM TENTANG HAK AZASI MANUSIA DALAM UUD 1945 BAGI WARGA PASIEN PROLANIS KLINIK PRATAMA RAHMATIKA SEMARANG - Muzayanah; Muhammad Zahrawan Qurrotaa’yun (Jurnal Pengabdian Kepada Masyarakat Media Ganesha, 2023)
The Republic of Indonesia is a constitutional state (rechtstaat), thus implementing a constitutional system based on the 1945 Constitution which we know as the constitution of the Republic of Indonesia. The 1945 Constitution establishes the legal basis for the Republic of Indonesia as a state of law, so that the government as administrator of the state and society must obey and adhere to the laws in force in the Republic of Indonesia. Every person who is located and domiciled in the territory of the Republic of Indonesia, be it a citizen or resident, then all of them are obliged to uphold Human Rights (HAM) which have been regulated in Chapter X concerning Human Rights, especially those regulated in Article 28 letter A up to Article 28 letter J of the 1945 Republic of Indonesia Constitution. Community Service Activities are the implementation of the Tri Dharma of Higher Education which must be carried out in order to provide understanding to the community. This community service activity has a target, namely residents of the Prolanis Program Pratama RAHMATIKA Clinic who is located at Pengkol hamlet R.T. 05/ R.T. 01, Ex. Mangunsari, Kec. Gunung Pati, Semarang City, is an Indonesian citizen who needs information and education related to their understanding of Human Rights (HAM) regulated in the 1945 Constitution. Considering that not all people and especially residents of this prolanis patient understand Human Rights or Human rights that must be upheld by every human being in the Republic of Indonesia, even universally in all parts of the world. The 1945 Constitution of the Republic of Indonesia regulates every citizen to understand, understand and uphold Human Rights (HAM). This legal counseling is important and very necessary for the residents of the Pratama RAHMATIKA Semarang clinic, because there are still many among these prolanis patients who do not understand and even unconsciously violate this human right. This legal counseling aims to provide understanding to the residents of Prolanis patients at this Clinic, so that it can be disseminated to their families, their living environment and the surrounding community and the wider community in general, so as to foster legal awareness to understand their rights and obligations and be able to obey and uphold Human Rights. Humans owned by every citizen of the Republic of Indonesia and carry out with full sense of responsibility.